WhatsApp as a Learning Tool: Investigating Gender Perspectives in English Education - Juhaepa Juhaepa; Hanna Hanna; Aderlaepe Aderlaepe (Journal of Language Education and Educational Technology (JLEET), 2023)
This research aims to assess students’ perceptions of WhatsApp as a learning tool in English education, explore gender differences in these perceptions, and analyze the challenges students face in utilizing WhatsApp for English learning. The study population consisted of tenth and twelfth-grade students from SMK Negeri 5 Kendari, totaling 112 students, with a sample size of 87 students. Data were collected through a questionnaire on students’ perceptions of WhatsApp and open-ended questions. The research design employed a mixed methods approach. The findings indicate a generally positive attitude among students at SMK Negeri 5 Kendari towards WhatsApp as a learning tool for English education. Moreover, a significant gender difference was observed, with male students showing a higher mean perception score compared to female students (p < 0.05). Male students tend to perceive WhatsApp more favorably as a learning tool for English. Additionally, the research identified two main challenges faced by students during online learning via WhatsApp: limited access to materials due to poor internet connection and difficulties in understanding teacher explanations delivered through WhatsApp. These findings underscore the potential of WhatsApp to enhance the English learning environment and outcomes. It is hoped that English teachers will take these findings into account to optimize the use of WhatsApp for English education.